The prediction of difficult intubation in obese patients using mirror indirect laryngoscopy: A prospective pilot study - Budde, Arne O (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The incidence of difficult laryngoscopy and intubation in obese patients is higher than in the general population. Classical predictors of difficult laryngoscopy and intubation have been shown to be unreliable. We prospectively evaluated indirect mirror laryngoscopy as a predictor of difficult laryngoscopy in obese patients. MATERIALS AND METHODS: 60 patients with a body mass index (BMI) greater than 30, scheduled to undergo general anesthesia, were enrolled. Indirect mirror laryngoscopy was performed and was graded 1-4 according to Cormack and Lehane. A view of grade 3-4 was classified as predicting difficult laryngoscopy. Additional assessments for comparison were the Samsoon and Young modification of the Mallampati airway classification, Wilson Risk Sum Score, neck circumference, and BMI. The view obtained upon direct laryngoscopy after induction of general anesthesia was classified according to Cormack and Lehane as grade 1-4. RESULTS: Sixty patients met the inclusion criteria; however, 8 (13.3%) patients had an excessive gag reflex, and examination of the larynx was not possible. 15.4% of patients who underwent direct laryngoscopy had a Cormack and Lehane grade 3 or 4 view and were classified as difficult. Mirror laryngoscopy had a tendency toward statistical significance in predicting difficult laryngoscopy in these patients. CONCLUSIONS: This study is consistent with previous studies, which have demonstrated that no one individual traditional test has proven to be adequate in predicting difficult airways in the obese population. However, the new application of an old test - indirect mirror laryngoscopy - could be a useful additional test to predict difficult laryngoscopy in obese patients.